2017
DOI: 10.1139/facets-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption is inversely associated with type 2 diabetes in Manitoba First Nations communities

Abstract: Consumption of fish and n-3 fatty acids (n-3 FAs) has been postulated to prevent type 2 diabetes (T2D). Objective: To explore the association between self-reported T2D and fish consumption, dietary n-3 FAs, and persistent organic pollutants (POP) intake in a regionally representative sample of First Nations (FNs) in Manitoba. Design: Data from the cross-sectional First Nations Food, Nutrition and Environment Study (FNFNES) collected from 706 members of 8 Manitoba FNs in 2010 were used. Household interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…The discrepancies in our findings reported in the previous studies in two groups of First Nations living in Manitoba and Ontario reflect differences in contaminant levels in fish species [ 36 , 37 ]. In fact, the concentrations of total PCBs and DDE in the most consumed fish species were estimated to be significantly higher in Ontario than in Manitoba.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The discrepancies in our findings reported in the previous studies in two groups of First Nations living in Manitoba and Ontario reflect differences in contaminant levels in fish species [ 36 , 37 ]. In fact, the concentrations of total PCBs and DDE in the most consumed fish species were estimated to be significantly higher in Ontario than in Manitoba.…”
Section: Discussioncontrasting
confidence: 96%
“…First, we compared the dietary intake and lifestyle habits between participants recently diagnosed with T2D (0–5 years) and individuals who had had T2D for a longer period of time (>5 years). The results showed that there were no statistically significant differences in dietary and lifestyle characteristics between the two groups in both Ontario and Manitoba First Nations [ 36 , 37 ]. Additionally, using data on self-reported dieting status, we examined whether dieting (i.e., limiting their caloric intake in order to lose weight) and non-dieting individuals with and without T2D differed by macronutrient intakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most health impacts documented among IPs are mediated through the consumption of polluted water (Huseman and Short 2012; Dudarev et al 2013; Bradford et al 2016) and food (Bordeleau et al 2016), including wild foods obtained through hunting (Cartró‐Sabaté et al 2019), fishing (Marushka et al 2017), and gathering (Strand et al 2002). Because IPs often eat animal parts where pollutants accumulate (e.g., fatty tissues), their exposure is higher than among nonindigenous groups who discard these parts.…”
Section: Resultsmentioning
confidence: 99%
“…Most research on local Indigenous food systems focuses on health outcomes, environmental impacts, or cultural aspects. Healthrelated traditional food research focuses primarily on food-tohealth outcomes, emphasizing the unique nutrient profiles and high nutritional value of traditional foods (Kuhnlein and Receveur 2007, Johnson-Down and Egeland 2010, Egeland et al 2011, Kenny et al 2018b; their contributions to food security (Lambden et al 2007, Power 2008, Kasimba et al 2018 and reduced incidence of chronic health conditions, including diabetes and obesity (Young et al 2000, Milburn 2004, Egeland et al 2011, Marushka et al 2017; and their role in food-borne contaminant and disease exposure (Kuhnlein and Chan 2000, Donaldson et al 2010, Quinn et al 2012, Dudley et al 2015, Binnington et al 2016. Environment-related traditional food research focuses primarily on environment-to-food impacts, emphasizing the climate vulnerability of traditional food systems (Krupnik and Jolly 2002, Furgal and Seguin 2006, Ford 2009, Royer 2015, including observed changes in the abundance and health of harvested species (Wassmann et al 2011, Dinero 2013, Kenny et al 2018a) and the increased difficulty and risk of Ecology and Society 25(2): 8 https://www.ecologyandsociety.org/vol25/iss2/art8/ Fig.…”
Section: Introductionmentioning
confidence: 99%